Sistem kendali kestabilan attitude quadrotor dengan metode self-tuning Fuzzy-PD - Sumardi Sumardi; Hadha Afrisal; Wisnu Dyan Nugroho (Jurnal Teknologi dan Sistem Komputer, 2020)
This research aims to develop a quadrotor control system for maintaining its position and balance from disturbance while hovering. A fast and reliable control technique is required to respond to high maneuverability and high non-linearity of six degrees of freedom system. Hence, this research focuses on designing a Self-Tuning Fuzzy-PD control system for quadrotor’s attitude. The designed control system utilizes input data from the Inertial Navigation System (INS). Then the quadrotor’s attitude is controlled by passing the PWM signal to the flight controller APM 2.6. The result shows that the average absolute error for the roll, pitch, and yaw angles are relatively small, as mentioned consecutively 2.079o, 2.266o, and 1.528o, while the maximum absolute errors are 6.314o, 6.722o, and 3.82o.